Enhancing Qualitative Health Education Achievement Among Secondary School Students in Anambra State Through Cooperative Learning Method - Orajekwe Veronica Ngozi (PT. Pusmedia Group Indonesia, 2025)
Quality teaching and learning of Health Education depends partly on use of a teaching method whose activities target most learning senses. This study sought to examine how the co¬operative learning method (CL) affects students' achievement In Health education. The study was guided by four null hypotheses. Using a non-equivalent control group design with 160 randomly selected students, the study found that CL method facilitated students7 Health Education Achievement more than regular methods. Gender did not affect achievement. Since CL method benefited students irrespective of gender, education authorities should encourage Health Education teachers to use it and teacher educators to make it part of the teacher-training curriculum